Error Analysis on Unindra Student’s Sentence Tenses Assignment - Sjafty Nursiti Maili (Deiksis, 2018)
Knowing the pattern of tenses is very important to the students, because it can help them to do a good sentence. If the students unknown the pattern of using tenses in sentences, the students are confused to make a good sentence. The teacher should try to correct their error by error analysis. Error analysis is really very important to students, because teachers know the mistaken students done in making a sentence by using in each tenses. In this study, the researcher used descriptive method which is the data was taken by student’s an assignment at the first students of UNINDRA. First, teachers asked students to make sentences based on eight tenses. They are Present Tense; Present Continuous Tense; Present Perfect Tense; Simple Future Tense; Past Tense; Past Continuous Tense; Past Continuous Tense; Past Perfect Tense; Future Perfect Tense. Second, After doing sentences in each tenses, the research done identify based on the pattern of sentences; Third, the last steps researcher analysis the assignment in make the table consist of table 1 the amount of error done; table 2 the error sentences students and correction; table 3 the reasons why sentences are difficulties to the students and easier. The results of these study 60 percentages students UNINDRA made good sentences in eight tenses; 40 percentages did not remember the pattern of tenses; 30 percentages made the error of changed verb; 30 percentages used time action to make sentence in each tenses.Key words; Tenses, Assignment, Error, Analysis, Pattern